Identification of joint swelling in pigs using infrared thermography - Caldara, F. R. (2015)
This study aimed to evaluate the effectiveness identifying joint edema in swine using the infrared thermal image. Data collection took place in a swine farm located in Brazil. Five castrated pigs with a mean weight of 60 kg were randomly selected amongst those presenting slight lameness and joint edema hardly noticeable at a sight. Infrared images were taken with a thermal visor Testo®. Ten points were selected in each limb, and the average of the surface temperature values were calculated. Mean values were tested using the t-Student test. The mean values of skin surface temperature were lower (p < 0.05) in the healthy limb than in the leg with joint edema (33.5 and 35,5°C, respectively). The difference was of approximately 2.0 °C and it helped the identification of the joint inflammation. Infrared thermography has been used to detect slight difference in skin temperature that may not be seen under normal circumstances. In the present study, the infrared images were useful to identify joint lesions in pigs. The use of infrared thermography showed potential for identifying lameness in pre slaughter conditions.